Mechanisms of amphetamine action illuminated through optical monitoring of dopamine synaptic vesicles in Drosophila brain - Zachary Freyberg (Nature Portfolio, 2016)
Amphetamines are known to enhance extracellular dopamine levels, but the underlying mechanisms are unclear. Utilising a new pH biosensor for synaptic vesicles, the authors show that amphetamines diminish vesicle pH gradients, disrupting dopamine packaging and leading to increased neurotransmitter release.